2002
DOI: 10.1007/s11745-002-0858-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and endothelium‐dependent vasodilation—A review

Abstract: Studies using both in vitro and in vivo techniques have repeatedly shown that endothelium-dependent vasodilation (EDV) is impaired in different forms of experimental as well as human hypercholesterolemia. Clearly this impaired EDV can be reversed by lowering cholesterol levels by diet or medical therapy. Competitive blocking of L-arginine, changes in nitric oxide synthase activity, increased release of endothelin-1, and inactivation of nitric oxide due to superoxide ions all contribute to the impairment in EDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 294 publications
0
21
0
Order By: Relevance
“…Each of these abnormalities are considered risk factors for type 2 diabetes and cardiovascular disease. Hypertriglyceridemia and low HDL cholesterol have been independently associated with endothelial dysfunction and inflammation [53].…”
Section: Dyslipidemia and Hypertensionmentioning
confidence: 99%
“…Each of these abnormalities are considered risk factors for type 2 diabetes and cardiovascular disease. Hypertriglyceridemia and low HDL cholesterol have been independently associated with endothelial dysfunction and inflammation [53].…”
Section: Dyslipidemia and Hypertensionmentioning
confidence: 99%
“…Although cholesterol clearly impacts endothelial cell function (37,38), the direct effects of cholesterol on endothelial gene expression have not been investigated. We previously reported that cholesterol negatively regulates the expression of COX-2 in vascular endothelial cells (19).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Ageing is characterized not only by a reduced arterial compliance and alteration of the contractile properties of the vascular wall, but also by endothelial dysfunction (Alvarez de Sotomayor, et al, 2005;Brandes et al, 2006). At present, there are several reasons to believe that in vivo NO synthesis from L-arginine could indeed be impaired in atherosclerosis, hypertension, dyslipidemia, diabetes, obesity, insulin resistance, metabolic syndrome, as well as in ageing (Lind, 2002;Laroia et al, 2003;Hsueh & Quinones, 2003;Holvoet et al, 2003Holvoet et al, , 2008aVickers et al, 2009;Park et al, 2009;Njajou et al, 2009;Huang, 2009;Park et al, 2011;Tabit et al, 2010). Recent studies support the fact that advancing age increases the LDL susceptibility to oxidation and decreases the nitric oxide availability and bioactivity .…”
Section: Oxidized Ldl and No Endothelial Synthesis As Factors Affectimentioning
confidence: 99%